105k views
5 votes
Dose anyone know this? Like I'm confused on what to do.

4×2×(-3)+(-10)÷5​

User JacoSolari
by
5.3k points

2 Answers

4 votes

Answer:

start with the prostheses first and the -3 and -10 together us

Explanation:

Please

excuse

my

dear

ant

sally

User Satvik
by
5.4k points
5 votes

Answer:

-26

Explanation:

4×2×(-3)+(-10)÷5​

=(8)(−3)+−10/5

=−24+−10/5

=−24+−2

=−26

User Adisheshu RY
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.